Vaccine prevention of rotavirus infection: Social significance and effectiveness - A. G. Yuzhakova; G. P. Martynova (Журнал инфектологии)
The rotavirus is the leading etiologic factor of intestinal infections. Epidemiological studies confirm the high prevalence of rotavirus gastroenteritis in children up to 5 years. WHO recommends the inclusion of routine vaccination against rotavirus infection in the national immunization programs of all countries with 2009. The article presents the experience and results of the introduction of vaccination against tear among children on the territory of Achinsk in Krasnoyarsk region.Objective: to evaluate the effectiveness of the regional program of immunization of children on the territory of Achinsk in Krasnoyarsk region, with pentavalent rotavirus vaccine (PVRVV) (Merck, Sharp & Dohme Corp., USA, LP- 001865 dated 10/01/2012).Methods.1267 children were immunized with PVRVV (80,0% of the newborn cohort) in the period July 2015 – June 2016: V1 – 1267; V2 – 918; V3 – 815. The vaccine was introduced, both independently and simultaneously with other vaccines of the Russian National Immunization Calendar (NIC), except for BCG (BCG-m). The immunization effect was evaluated in 2016 compared to 2014 (doubtingly period): reduction of IIs hospitalizations among 0-3 years old cohort, and reduction of IIs outpatient visits among pediatric and adult patients.Results. Demonstrated safety and good tolerability of PVRVV, the overall rate of adverse events constituted 6,4±0,7, the possibility of combination with other vaccines of the NIC, no side effects with self-administration, reduction of IIs hospitalizations in 0–12 months years old group of vaccinated by 39,1%; among children not subject to vaccination (12–36 months) by 26,5%; the reduction of IIs outpatient visits both among pediatric and adult population.Conclusion. Our study confirms numerous global observations of the fact that the RVI vaccination is one of the best ways to control the RVI incidence rate, thereby improving the socio-economic population well-being through preservation of life and health in children.